Corrosion kinetics of an alloy immerged into a liquid melt containing oxygen - Bakai, A.S.; Tanatarov, L.V. (Вопросы атомной науки и техники, 2005)
Corrosion kinetics of a metal in metallic coolant containing oxygen is considered. The corrosion rate is found. The oxide film growth kinetics at moderate and high over-saturations of the oxygen content in coolant is considered. A mechanism of the oxide film growth blocking is described.